Concurrent and Selective Determination of Dopamine and Serotonin with Flexible WS2/Graphene/Polyimide Electrode Using Cold Plasma. Issue 45 (23rd September 2021) - Kim, Hyeong‐U; Koyappayil, Aneesh; Seok, Hyunho; Aydin, Kubra; Kim, Changmin; Park, Kyu‐Young; Jeon, Nari; Kang, Woo Seok; Lee, Min‐Ho; Kim, Taesung
Abstract: Makers of point‐of‐care devices and wearable diagnostics prefer flexible electrodes over conventional electrodes. In this study, a flexible electrode platform is introduced with a WS2 /graphene heterostructure on polyimide (WGP) for the concurrent and selective determination of dopamine and serotonin. The WGP is fabricated directly via plasma‐enhanced chemical vapor deposition (PECVD) at 150 °C on a flexible polyimide substrate. Owing to the limitations of existing fabrication methods from physical transfer or hydrothermal methods, many studies are not conducted despite excellent graphene‐based heterostructures. The PECVD synthesis method can provide an innovative WS2 /graphene heterostructure of uniform quality and sufficient size (4 in.). This unique heterostructure affords excellent electrical conductivity in graphene and numerous electrochemically active sites in WS2 . A large number of uniform qualities of WGP electrodes show reproducible and highly sensitive electrochemical results. The synergistic effect enabled well‐separated voltammetric signals for dopamine and serotonin with a potential gap of 188 mV. Moreover, the practical application of the flexible sensor is successfully evaluated by using artificial cerebrospinal fluid. Abstract : Innovative fabrication method for a bunch of flexible electrodes with a WS2 /graphene heterostructure is developed by using plasma‐enhanced chemical vapor deposition. Low‐temperature (150 °C) process enables direct fabrication on polyimide with a simple process, with 12 electrodes simultaneously fabricated with high reproducibility. The flexible biosensor enables well‐separated voltametric signals for dopamine and serotonin and is evaluated by using artificial cerebrospinal fluid.